PENGEMBANGAN LKS SEGITIGA DAN SEGI EMPAT BERBASIS PENDEKATAN OPEN-ENDED PADA PEMBELAJARAN MATEMATIKA KELAS VII SMPN 1 BASO - Kasmawati, Kasmawati; Yenti, Isra Nurmai; Zulmardi, Zulmardi (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research is to produce a valid and practical LKS which based open-ended approach. This research is a kind of research and development whose three stages of reseach, including front-end analysis, prototype and assesment. Technique of data analysis is done by descriptive analysis. From the result of this reserach, it was produced the valid and practical LKS which based open-ended approach for triangle and rectangle material for the first grade of junior high school. Validity, according math experts, means after revising and practicality means after trying out toward students of first grade of SMP 1 Baso. So LKS based open-ended forÂ triange and rectangle material which constructed by researcher has been valid from form, content and language used. LKS based open-ended approach for triangle and rectangle material which constructed by the researcher has been practical.Key words: LKS berbasis pendekatan open-ended, Â segitiga dan segi empat, validitas praktikalitas